Idiopathic Organ Transplant Chorioretinopathy after Liver Transplantation. (16th March 2015) - Abalem, Maria Fernanda; Carricondo, Pedro Carlos; Pimentel, Sergio Luis Gianotti; Takahashi, Walter Yukihiko
Abstract : Idiopathic organ transplant chorioretinopathy is a rare disease associated with kidney and heart transplantation. We present a case secondary to liver transplantation including its multimodal imaging, differential diagnosis, and physiopathology discussion.